Contributions to contamination dynamics, assessment and remediation of the environment : application for the degree of Doctor of Science DSc from Massey University, Palmerston North, New Zealand - Naidu, Ravendra (Massey University, 2015)
Environmental contamination is a massive problem for Australia and, indeed, globally. It has serious impacts on: • human health; • the health and sustainability of our natural environment; and • the economy. Historical environmental contamination will be a toxic legacy for Australians for decades to come. There are over 160,000 potentially contaminated sites in Australia. Remediation is currently costing companies and owners of contaminated sites in excess of $3 billion per annum, with the number of sites remediated being less than 5%. Cases of poisoning by substances such as arsenic, lead, asbestos, pesticides etc. are in the news almost daily, while large areas of valuable land (for example in China) cannot be used because of past contamination. Surface and subsurface soil and its groundwater environment is a complex and heterogeneous system. Once contaminants have come into contact with these systems, assessment and remediation is difficult and extremely challenging. Australia has not yet developed the affordable solutions, the preventative technologies and advanced regulatory frameworks to address this huge problem and curb its spread. Professor Naidu, a PhD graduate of Massey University, recognised environmental contamination as a major challenge confronting the community, owners of contaminated sites and regulatory bodies as early as the 1990s - before Australia even had its National Environment Protection Measure in, place. Recognising the gap in knowledge on contaminants, he commenced a research and technology development program providing initial leadership in Australia and later internationally by heading Commission 3.5 (2002 to 2010) which focused on Soil Degradation and Reclamation. He also raised in excess of $500 million to establish a Co-operative Research Centre for Contamination Assessment and Remediation of the Environment (CRC CARE) - the only National Centre of Excellence that focuses on contamination and remediation. The research undertaken within this Centre is prioritised through extensive consultation and participation by end-users. Since commencing research on contaminants, Professor Naidu has enhanced our understanding of risks posed by contaminants in the environment, their fate and behaviour in soil and groundwater, and techniques for assessing and remediating contaminated sites. These areas are grouped, in this thesis, into five overlapping areas of research: • Measurement; • Fate and dynamics; • Bioavailability; • Food Chain and • Remediation. The key elements of these five themes, and their contribution to knowledge, form Chapters 2-6 of the thesis. Professor Naidu's awards and honours are summarised in his curriculum vitae.
This Doctor of Science comprises a number of published works, listed in the file attached. Due to copyright restriction they are not included here but can be accessed individually from the publisher.
Keywords: Soil remediation; Environmental engineering